Doing justice better : the politics of restorative justice - Cornwell, David J. (Waterside Pr. ; North American distributor ISBS, 2007)
An uncompromising appraisal of the unique penal crisis affecting Britain and other Western-style democracies. Escalating resort to prisons, longer sentences, overcrowded and ineffective regimes, high rates of re-offending and eclectic penal policy all combine to fuel this crisis, whilst failing to reduce offending. In this new book, David J Cornwell, author of the acclaimed Criminal Punishment and Restorative Justice (ISBN 9781904380207), argues that the symptoms of this penal malaise are grounded in media sensationalism of crime and the need of politicians and their advisers to retain electoral credibility. Change is long overdue, but it requires a fresh, contemporary penology based on Restorative Justice. The book challenges the status quo, asks 'different questions' and places victims of crime at the centre of the criminal justice process.